Leo Strauss on Plato's Euthyphro : the 1948 notebook, with lectures and critical writings - Strauss, Leo (The Pennsylvania State University Press, 2023)
"An examination of Leo Strauss's 1948 notebook and other writings on the Euthyphro, Plato's dialogue on piety, using close analysis and line-by-line commentary"-- Provided by publisher.
Includes the text of Plato's Euthyphro in Greek with English translation.
Keywords: Plato. -- Euthyphro.; Euthyphro (Plato); Piety.; Piété.; PHILOSOPHY / Political; Piety; .; Crito.; Euthyphro.; Jerusalem and Athens.; Leo Strauss.; Plato.; Seth Benardete.; Socrates.; ancient philosophy.; classical political philosophy.; hermeneutics.; neoconservativism.; philosophy of religion.; philosophy.; piety.; religion.; theology.